Reformulation of Legal Regulations for Battery-Based Electric Vehicle Use and Battery Waste Management in Indonesia - Imam Mustakim; Indah Kusuma Wardhani (Indonesian Journal Publisher, 2026)
This study aims to analyze and propose reforms to the legal regulations governing the use of battery-based electric vehicles and the management of battery waste in Indonesia, from the perspectives of environmental law and sustainable development. The method used is a normative juridical approach, with a legislative and conceptual approach, based on a review of Law Number 32 of 2009, Government Regulation Number 22 of 2021, and Presidential Regulation Number 55 of 2019. The results indicate that existing legal regulations remain sectoral, do not fully accommodate the battery life-cycle approach, and contain inconsistencies and gaps in norms, particularly regarding producer responsibility and post-use battery waste management. These conditions have the potential to create environmental pollution risks and legal uncertainty amidst the accelerating energy transition. Therefore, an integrative legal reformulation based on the principles of sustainable development, a circular economy, and Extended Producer Responsibility is needed through the establishment of specific regulations, strengthening oversight mechanisms, and developing a national battery recycling industry to achieve effective and equitable environmental protection.